THE IMPACT OF THE DEVELOPMENT OF INSTITUTION REPOSITORY AS INFORMATION SERVICE IN THE LIBRARY OF TRUNOJOYO MADURA UNIVERSITY IN THE KNOWLEDGE MANAGEMENT CONTEXT - BAKHTIYAR; DEASY INDRIANINGTYAS (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This research aims to describe the impact of developing the knowledge of the UPT Trunojoyo University Madura repository as appropriate at this time. Research aims to examine the analysis of content studies focusing on the development of institutional repositories. Libraries are required to support the achievement of Worl Class University’s vision and mission, so that libraries are required to open access to all intellectual products to the public. Research includes in-depth analysis, based on a major study of various reasons for the development of institutional repositories. Research analysis requires critical thinking, for the application of concepts in historical and past history, so that it is appropriate to use a historical approach, characterized by a critical inquiry into the development of a thought or term. Primary information sources are important elements as primary data. Data collection prioritizes the use of library research through the activity of reading literature materials. Descriptive qualitative analysis, with sources of analysis of theoretical reading, research and non- research. The research prioritizes the description and evaluative factual facts to obtain solutions to various problems that arise in the phenomenon of institutional repository development. In order to validate the analysis, content analysis is needed, analyzing the meanings of important concepts of the role of libraries, open access to information, developing institutional repositories. Observation in the library, empowered to construct the theory. Comparative analysis is used to conduct various comparisons before and after the development of institutional repositories. The results of the study are; (1). the development of institutional repositories by UPT Trunojoyo University Madura must be followed; (a) information technology application, (b) good information management application, (c) professionalism and quality of librarians. (2). Institutional deposits, ie products of scientific work, research results, theses, theses, etc., must be openly accessible through institutional repositories. (3). Institutional repositories really need to be developed through software applications to be indexed by Google and webometrics, which finally Trunojoyo Madura University can achieve the vision and mission of the ward class university.